SUPPORT WITH CLARITY: A PROPER TREND IN MEDICAL STATISTICS - Tang, Bing H. (Journal of Ayub Medical College Abbottabad, 2006)
Background: The aim of this study was to establish effective methods to review and evaluate, and to emphasize in support with clarity as a proper trend in medical statistics. Methods: The clinical research material used in this study is stemmed from JAMC. Study:I, N is 220 subjects, from Pattern of Coronary Arterial Distribution and Its Relation to Coronary Artery Diameter, Z A Kaimkhani, MM Ali, AMA Faruqi JAMC Jan-Mar 2005; 17(1): 40-3.1 Study:II, N is 105 patients, from Sclerotherapy Plus Octreotide Versus Sclerotherapy Alone In The Management Of GastroOesophageal Variceal Hemorrhage. HA Shah, K Mumtaz, W Jafri, S Abid, S Hamid, A Ahmad, Z Abbas. JAMC Jan-Mar 2005; 17(1): 10-4. 2 Systemic review and evaluation with statistical principles is to be used. Assessment and discussion: The reports of 2 clinical researches from JAMC are assessed, and both used for demonstrating the characteristics and pitfalls statistically. Conclusion: Before reaching any significant difference in statistics, hopefully, all clinicians will be able to deal with the data to be measured by selecting proper statistical models as the best as we can in order to gain appropriate inference in medical statistics. Key words: Regression, prediction, correlation, survival, variable